2006
DOI: 10.1088/0954-3899/32/6/r01
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies with the use of deep-inelastic heavy-ion reactions

Abstract: Gamma spectroscopic studies exploiting deep-inelastic heavy-ion reactions in thick target experiments are reviewed. The description of physical motivation, history of early experiments, analysis of the N/Z equilibration process as well as the outline of the experimental method and data analysis are followed by the presentation of main results obtained in various regions of the nuclide chart. Brief comments on thin target spectroscopy experiments involving fragment detection and future outlook are summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 100 publications
7
123
0
Order By: Relevance
“…In all three measurements deep-inelastic reactions with heavy ions were used to populate excited states in the isotope of interest. The first experiment, performed at the Argonne National Laboratory ATLAS accelerator, was part of a series of thick-target, γ-coincidence studies aimed at the spectroscopy of neutron-rich nuclei inaccessible in fusionevaporation reactions [14]. The 330-MeV 48 Ca beam was impinging on a 50 mg/cm 2 -thick metallic 238 U target placed at the center of the Gammasphere multidetector array [15].…”
Section: Experiments Data Analysis and Resultsmentioning
confidence: 99%
“…In all three measurements deep-inelastic reactions with heavy ions were used to populate excited states in the isotope of interest. The first experiment, performed at the Argonne National Laboratory ATLAS accelerator, was part of a series of thick-target, γ-coincidence studies aimed at the spectroscopy of neutron-rich nuclei inaccessible in fusionevaporation reactions [14]. The 330-MeV 48 Ca beam was impinging on a 50 mg/cm 2 -thick metallic 238 U target placed at the center of the Gammasphere multidetector array [15].…”
Section: Experiments Data Analysis and Resultsmentioning
confidence: 99%
“…[2] and references therein). Examples from the present studies, where isomers have provided the sensitivity required to study nuclei that are difficult to access, include the cases of 206 Hg [3] and 211 Pb [4].…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered by Perlman et al [6] in 1962 at a time when α-particle spectroscopy of long-lived states was already well developed. Glendenning [7] explained that the unusually high α-decay hindrance was caused by the high spin of the isomeric state, suggesting an 18 + assignment and an associated maximally-aligned, πh 2 9/2 νi 2 11/2 four-particle configuration. The absence of a γ-decay branch was understood by the state lying so low in excitation energy that the only possible γ-ray decay pathways were via low-energy, high-multipolarity transitions that are not favoured compared to α emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also common for particle-evaporation from the beam-like and target-like reaction products to follow the primary reaction. Broda et al [16,17] found that, typically, a few nucleons are lost, generally neutrons, so that the coincident beam-like and target-like reaction products are not necessarily specified uniquely.…”
Section: Isotopic Assignmentsmentioning
confidence: 99%